Kinetics of Thermodegradation of Palm Kernel Oil Derived Medium-Chain-Length Polyhydroxyalkanoates - Sin, M.C.; Tan, I.K.P.; Annuar, M.S.M.; Gan, S.N. (Wiley, 2012)
Oligomeric hydroxyalkanoic acids have potential industrial, medical, and pharmaceutical applications and they can be produced from the degradation of high molecular weight polyhydroxyalkanoates by a number of different ways. Thermal decomposition takes place in the absence of organic solvent and other chemicals and this justified the method of producing low molecular weight PHA as green chemistry. The kinetics for thermal degradation of medium-chain-length polyhydroxyalkanoates (mcl-PHA) prepared from saponified palm kernel oil (SPKO) was studied by thermogravimetric analysis (TGA) technique. Employing the nonisothermal Kissinger's method, the degradation activation energy, E d, and pre-exponential factor, A, were 129 kJ mol -1 and 1.15 Ã 10 10 s -1, respectively. Specific degradation rate constant, k was found to increase at higher heating rate. Â© 2012 Wiley Periodicals, Inc.